Optimization of hydrolysis conditions for the production of oriental angel wing (Pholas orientalis) hydrolysate by Protamex: effect of time and enzyme substrate ratio / Emilia Azrina Mohd Bakri. - Mohd Bakri, Emilia Azrina (2009)
In this study, oriental angel wing {Pholas orientalis) hydrolysate was hydrolyzed by using Protamex. The total protein content in oriental angel wing per lOOg sample was 12%. Hydrolysis conditions were optimized by using response surface methodology (RSM). The model equations were proposed with regard to the effects of time (min) and enzyme substrate ratio (%) on the degree of hydrolysis (DH) and nitrogen recovery (NR). By fitting the experimental data to the equation, the DH optimum levels for time (180min), ES (6%), %DH (5.11%) with desirability 0.596 at constant pH 7 and constant temperature 50°C were obtained. For %NR, the optimum levels for time (92.44 min), ES (3.21%), %NR (0.972%) with the desirability 0.935 were obtained. This study is important to any researcher to make a further analysis regarding the activity of enzyme hydrolysis especially when dealing with endoproteinase enzyme such as Protamex. This study also had open the opportunity for those who want to do further study on the sample namely oriental angel wing (Pholas orientalis) which is not yet popular among scientist. It also help to increase the economical support for those who supplied these bivalve species.